Pregnancy and diabetic ketoacidosis: fetal jeopardy and windows of opportunity - Coetzee, Ankia; Hall, David R.; Langenegger, Eduard J.; van de Vyver, Mari; Conradie, Magda (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Diabetic ketoacidosis (DKA) during pregnancy poses significant risks to both the mother and fetus, with an increased risk of fetal demise. Although more prevalent in women with Type I diabetes (T1D); those with Type 2 diabetes (T2D) and gestational diabetes mellitus (GDM) can also develop DKA. A lack of information about DKA during pregnancy exists worldwide, including in South Africa.Objective: This study examined the characteristics and outcomes associated with DKA during pregnancy.The study took place between 1 April 2020 and 1 October 2022. Pregnant women with DKA, admitted to Tygerberg Hospital's Obstetric Critical Care Unit (OCCU) were included. Maternal characteristics, precipitants of DKA, adverse events during treatment, and maternal-fetal outcomes were examined.Results: There were 54 episodes of DKA among 47 women. Most DKA's were mild and occurred in the third trimester. Pregestational diabetes dominated (31/47; 60%), with 47% having T1D and 94% requiring insulin. Seven women (7/47, 15%; T2D:6, T1D:1) had two episodes of DKA during the same pregnancy. Most women (32/47; 68%) were either overweight or obese. Yet, despite the T2D phenotype, biomarkers indicated that auto-immune diabetes was prevalent among women without any prior history of T1D (6/21; 29%). Twelve women (26%) developed gestational hypertension during pregnancy, and 17 (36%) preeclampsia. Precipitating causes of DKA included infection (14/54; 26%), insulin disruption (14/54; 26%) and betamethasone administration (10/54; 19%). More than half of the episodes of DKA involved hypokalemia (35/54, 65%) that was associated with fetal death (P=0.042) and hypoglycemia (28/54, 52%). Preterm birth (<37 weeks' gestation) occurred in 85% of women. No maternal deaths were recorded. A high fetal mortality rate (13/47; 28%) that included 11 spontaneous intrauterine deaths and two medical terminations, was observed.Women with DKA have a high risk of fetal mortality as well as undiagnosed autoimmune diabetes. There is a strong link between maternal hypokalemia and fetal loss, suggesting an opportunity to address management gaps in pregnant women with DKA.